Optimization of trace metal composition utilizing Taguchi orthogonal array enhances biomass and superoxide dismutase production in Tetraselmis chuii under mixotrophic condition: implications for antioxidant formulations - Chan, Chiu Peng; Ni, Huang Zhen; Pannerchelvan, Sangkaran; Halim, Murni; Tan, Joo Shun; Kasan, Nor Azman; Mohamed, Mohd Shamzi (Springer Science and Business Media Deutschland GmbH, 2025)
The natural ageing process in all organisms is majorly influenced by the production rate and dismutation of reactive oxygen species (ROS) within cells. Certain microalgae, such as Tetraselmis chuii, possess the ability to produce superoxide dismutase (SOD), a powerful antioxidant enzyme that mitigates oxidative damage caused by ROS during oxygen metabolism. This study investigated the impact of trace elements (nickel, manganese, copper, zinc, and iron) and nitrogen sources in the growth medium on both the biomass and SOD synthesis of T. chuii under mixotrophic conditions. Initially, the one-factor-at-a-time (OFAT) approach was employed to filter out the most significant factors in the production medium. Next, Taguchi orthogonal array method, known for its robustness in experimental design, was employed to analyse the effects of various media components on algal biomass and SOD production. Using only a few well-defined experimental sets, Taguchi’s L18 orthogonal array facilitated a 1.21-fold increase in biomass yield, reaching a maximum of 0.643 g/L. Furthermore, SOD activity was enhanced from 85.28 to 91.94% following optimization. Notably, nitrogen source, nitrogen concentration, and zinc concentration emerged as significant influencers of biomass and SOD production. The Taguchi optimization thereby improved SOD yield in a cost-effective manner. The heightened antioxidation activity of SOD holds promising applications in formulating antioxidants and topical ointments in pharmaceutical and cosmeceutical industries.